Autoamputation of the Breast in Invasive Ductal Carcinoma: A Case Report - Olusola-Bello MA; Olatunji AA; Ayoade BA; Adekoya AO; Ogunlade SB (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2022)
Autoamputation is the spontaneous detachment from the body and elimination of an appendage or abnormal growth. Autoamputation of an organ due to malignancy has been reported in various organs, although its aetiopathogenesis has not been fully explained. Autoamputation of the breast is associated with late presentation and slow desmoplastic reaction in breast cancer. The patient was a 43- year- old Nigerian woman who presented with a one-year history of left breast mass diagnosed as triple negative invasive ductal carcinoma. She defaulted from hospital care but represented after autoamputation of the left breast. The case is reported to showcase the variations in the clinical course of breast cancers.